Valorization of Corn Cobs: A Sustainable Filtration Approach for Caffeine and Triclosan Removal - Villamar-Ayala, C (Springer Science and Business Media Deutschland GmbH, 2025)
The continuous occurrence of emerging contaminants, such as caffeine and triclosan in water sources, poses significant environmental and public health risks, particularly in decentralized low-income contexts. This study evaluated the performance of corn cobs (low-cost abundant agro-industrial by-product) used as filter medium for emerging contaminant removal. Laboratory-scale filters (height: 100 cm; diameter: 12 cm) were packed with corn cobs of different particle sizes—small (SPF: 0.8–2.0 cm), medium (MPF: 2.0–3.5 cm), large (LPF: 3.5–5.7 cm), and mixed (MxPF), operating under three hydraulic loading rates (1, 2, and 4 m3/m2·d) with intermittent feeding cycles (6 h/day). Prior to use, the corn cobs were washed, oven-dried at 80 °C, sieved, and characterized using ASTM standard methods, FTIR, BET, and SEM analyses. The MPF filter operated at 2 m3/m2·d showed the best overall performance, with up to 92.1% caffeine and 99.0% triclosan removal, without clogging (head losses: − 2.1–4.8 cm H₂O), and extended operational time (up to 246 h). Triclosan columns exhibited slower saturation, likely due to stronger interactions with the filter media driven by its higher molecular weight and hydrophobicity. Its antimicrobial properties may have also supported greater filter stability, a possibility that warrants further investigation. These findings underscore the potential of corn cob-based systems for water treatment/reclamation in decentralized low-income zones, promoting agricultural residues revaluation according to circular economy principles. © The Author(s) 2025.